2022
DOI: 10.1007/s10802-022-00930-4
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies between Subjective Reports of Cognitive Difficulties and Performance on Cognitive Tests are Associated with Elevated Internalising and Externalising Symptoms in Children with Learning-related Problems

Abstract: Children with learning difficulties are commonly assumed to have underlying cognitive deficits by health and educational professionals. However, not all children referred for psycho-educational assessment will be found to have deficits when their abilities are measured by performance on cognitive tasks. The primary aim of this study was to estimate the prevalence of this inconsistent cognitive profile (ICP) in a transdiagnostic sample of children referred by health and education service providers for problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Though the caregiver measures used in this study have been found to have good reliability, further study would benefit from understanding the psychological mechanisms which are associated with these co-occurring characteristics. Performing cognitive tasks (in addition to rating scales) to compare the findings in relation to reporting by caregivers, non-clinical, and clinical professionals could provide a more robust understanding of the psychological mechanisms underpinning the challenges experienced [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though the caregiver measures used in this study have been found to have good reliability, further study would benefit from understanding the psychological mechanisms which are associated with these co-occurring characteristics. Performing cognitive tasks (in addition to rating scales) to compare the findings in relation to reporting by caregivers, non-clinical, and clinical professionals could provide a more robust understanding of the psychological mechanisms underpinning the challenges experienced [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Joni's research group uses the core principles of empirical psychological research to provide mechanistic accounts of child development and understand childhood neurodevelopmental differences from a transdiagnostic perspective (e.g. Astle et al, 2018; 2022; Bathelt et al, 2018; Guy et al, 2022; Holmes et al, 2019; 2020; 2021; 2022; Mareva et al, 2019; 2023; Siugzdaite et al, 2020; Williams et al, 2022). Punit's research group focuses on neurodiversity in adulthood, including a pioneering body of work testing the strengths putatively associated with neurodivergence (e.g.…”
Section: Generalist Editorsmentioning
confidence: 99%
“…This unique transdiagnostic paediatric sample provides an opportunity to study the factors (genetics and environmental) and mechanisms that drive diversity in neurodevelopment, independent of categorical diagnoses and their co-occurrence. The CALM cohort is a well-characterised sample from the point of view of behavioural features (Bryant et al, 2020; Holmes, Mareva, et al, 2021; Mareva et al, 2023; Williams et al, 2022), dimensions of cognitive and executive functions (Bathelt et al, 2018; Holmes, Guy, et al, 2021; Mareva & Holmes, 2019), dimensions of mental health (Guy et al, 2022; Holmes, Mareva, et al, 2021), and neuroimaging (Akarca et al, 2021; Siugzdaite et al, 2020). The current paper addresses the question of whether and how Attention-Deficit/Hyperactivity Disorder (ADHD) and Intelligence PGS are associated with relevant neurodevelopmental characteristics within the transdiagnostic CALM sample.…”
Section: Introductionmentioning
confidence: 99%